Moving through cancer: Setting the agenda to make exercise standard in oncology practice - Schmitz, Kathryn H.; Stout, Nicole L.; Maitin‐Shepard, Melissa; Campbell, Anna; Schwartz, Anna L.; Grimmett, Chloe; Meyerhardt, Jeffrey A.; Sokolof, Jonas M. (Cancer, 2021)
LAY SUMMARY International evidence‐based guidelines support the prescription of exercise for all individuals living with and beyond cancer. This article describes the agenda of the newly formed Moving Through Cancer initiative, which has a primary objective of making exercise standard practice in oncology by 2029. International evidence‐based guidelines support the prescription of exercise for all individuals living with and beyond cancer. This article describes the agenda of the newly formed Moving Through Cancer initiative, which has a primary objective of making exercise standard practice in oncology by 2029.